2016
DOI: 10.1007/s11356-016-8067-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the edaphic factors and metal content in soil on the diversity of Trichoderma spp.

Abstract: Influence of edaphic factors and metal content on diversity of Trichoderma species at 14 different soil sampling locations, on two depths, was examined. Forty-one Trichoderma isolates from 14 sampling sites were determined as nine species based on their internal transcribed spacer (ITS) sequences. Our results indicate that weakly alkaline soils are rich sources of Trichoderma strains. Also, higher contents of available K and P are connected with higher Trichoderma diversity. Increased metal content in soil was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Some authors have described a high Cu-tolerance of Trichoderma spp. to a wide range of Cu concentrations [4349]. In this study, the toxic effect of CuSO 4 amended medium on the growth of Trichoderma spp., compared by the Dunnett’s test, was statistically significant in concentrations above 0.1% CuSO 4 for all strains (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have described a high Cu-tolerance of Trichoderma spp. to a wide range of Cu concentrations [4349]. In this study, the toxic effect of CuSO 4 amended medium on the growth of Trichoderma spp., compared by the Dunnett’s test, was statistically significant in concentrations above 0.1% CuSO 4 for all strains (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Some species belonging to the genus Trichoderma are used in the removal of toxic substances from soil (Harman et al, 2004). The greatest variability of Trichoderma species is in the soil top horizon, especially in the rhizosphere of different vegetables (Racić et al, 2016). Kredics et al (2001) have shown that selected strains of these fungi can bind heavy metals and thus make them less toxic to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Strain T. harzianum SZMC 20660 (deposited in the Szeged Microbiological Collection (SZMC); Department of Microbiology) was isolated from the A horizon (5-30 cm) of agricultural soil used in organic agriculture. Species determination was based on their internal transcribed spacer (ITS) sequences [64].…”
Section: Fungal Suspension Applicationmentioning
confidence: 99%